Digital dictionary system / Zaharah Ibrahim - Zaharah, Ibrahim (2004)
Digital dictionary conception of an electronic is quite distinct from the conventional online dictionaries that are now common. Digital dictionary is a global system and it is suitable for public usage. It is also so simple system that takes only a few minutes to learn. This idea is a great time saver for user and it is tricking down to everyday usage can serving a useful purpose for humanity. There are four main functions such as elaborate difficult words that involve a similar word for incorrect input from user the third function is this system developed with audio pronunciation and the last function the system is provided with example of elaboration and picture. A non functional requirement such as reliability, serviceability, portability, user-friendly and accuracy describes a restriction on the system that limits our choices for constructing a solution to the problem arises. Considering dictionary is always needed by each user in the specific fields especially such as education, business, research and etc. So I hope that this system can give satisfaction to user from all aspect.